Basic heat transfer - Kreith, Frank; Black, William Z. (New York : Harper & Row Publishers, Inc., 1980)
This book presents an introductory treatment of engineering heat transfer. It is a text designed for one-semester or a one-quarter course at the junior or senior level for engineering students in any of the classic disciplines.
1. Principles of heat transfer -- 2. Steady state conduction -- 3. Transient conduction -- 4. Analysis of convection heat transfer -- 5. engineering relations for convection heat transfer -- 6. Radiation -- 7. Heat exchangers -- 8. Condensation, boiling, and mass transfer
Keywords: HEAT -- TRANSMISSION